Biochemical and histological assessment of hepatic lipid in sudden infant death syndrome. Issue 10 (October 1983) - Cairns, S R; Thomson, M; Lawson, A M; Madigan, M J; Variend, S; Peters, T J
Abstract : A biochemical and histological study of hepatic lipid in children dying from the sudden infant death syndrome (SIDS) and children of a similar age dying explicably are reported. Contrary to a previous report based on histological assessment of hepatic lipid, no significant increase of total lipid content in livers of children dying from SIDS was found. Analysis of hepatic phospholipid fatty acid esters, however, revealed a significant difference between SIDS and children of similar age dying acutely and explicably. The phospholipid abnormality found in SIDS was similar to that found in children dying subacutely with hypoxia and would be consistent with increased cell membrane fluidity. The implications of these findings in the pathogenesis of SIDS are discussed.